Extensive reading as an integral part of teaching English as a foreign language - Katernyuk, V. (Continuing Professional Education: Theory and Practice, 2019)
This article is devoted to the problem of teaching foreign language students of the first and second years of study to read books in the original which is a part of extensive reading course. Extensive reading course is aimed at developing both reading and speaking skills as it includes active reading with answering questions, enriching vocabulary, and improving grammar. The author develops a system of exercises to improve students’ reading and speaking skills, vocabulary and creative thinking using Oscar Wilde’s play The Importance of Being Earnest. The exercises are divided into two types according to two stages the author suggests: a preparatory reading stage and a proficiency reading stage.